Formation of Hexagonally Packed Hollow Hoops and Morphology Transition in RAFT Ethanol Dispersion Polymerization - Zhang, Wen-Jian; Hong, Chun-Yan; Pan, Cai-Yuan (Macromolecular rapid communications., 2015)
Similar to the traditional self‐assembly strategy, polymerization induced self‐assembly and reorganization (PISR) can produce a myriad of polymeric morphologies through morphology transitions. Besides the chain length ratio (R) of the hydrophobic to the hydrophilic blocks, the chain mobility in the intermediate nano‐objects, which is a requisite for morphology transition, is a determining factor in the formation of the final morphology. Although various morphologies have been fabricated, hexagonally packed hollow hoops (HHHs) with highly ordered internal structure have not, to the best of our knowledge, been prepared by PISR. In this article, the fabrication of HHHs through morphology transition from large compound vesicles to HHHs is reported. HHHs with highly regular internal structure may have significance in theoretical research and practical applications of nanomaterials. Highly ordered assemblies with a hexagonally packed hollow hoops (HHHs) structure are successfully fabricated through morphology transition from large compound vesicles to HHHs in RAFT dispersion polymerization for the first time. Besides the chain length ratio (R) of hydrophobic to hydrophilic blocks, the chain mobility in the nano‐objects is a determining factor for morphology transition.